PHYSICAL EDUCATION IN YOUNGSTER AND ADULT EDUCATION (Fiep Bulletin - online, 2014)
The aim of this study is to identify the production of knowledge in the area of the physical education that has as an object of the physical education in Youngsters and Adults Education (Educação de Jovens e Adultos - EJA in Portuguese) in the libraries of ULBRA (Canoas), UNISINOS, FEEVALE, UFRGS and IPA universities. This production is expressed in books, final papers, reports and theses. In order to carry this survey the data base of the libraries of these universities had been consulted. At ULBRA/Canoas and at IPA, there are not materials related to physical education and EJA. At UNISINOS, we found a master's degree in Education. At FEEVALE, we found a final paper of the graduation course of in physical education. Moreover, at UFRGS, we found a final paper of the teaching course. We also consider the periodic that we found in the libraries, we read the magazines from their indexes, totalizing 206 units. However, we did not find articles referring to Youngsters and Adults Education. From this survey, we can point that there is a challenge for the universities, as well as for the scientific community. It is a challenge to provoke, to guarantee and to extend the debate of the issues in relation to physical education in the modality of EJA education.
Keywords: Physical education; Youngster and Adult Education; Production of knowledge